Tradeoffs in the Rehabilitation of a Succulent Karoo Rangeland. (14th May 2013) - Hanke, Wiebke; Wesuls, Dirk; Münchberger, Wiebke; Schmiedel, Ute
Abstract: Rangeland rehabilitation has multiple, sometimes conflicting goals, such as the reestablishment of the predisturbance vegetation, soil protection, and forage production. The rehabilitation techniques should be also cost‐effective and practicable. Given the difficulties and high costs of restoring Succulent Karoo rangelands and the continuously high grazing pressure in the communal lands, tradeoffs should be accepted in the achievement of these goals. We tested the capability of paddock manure redistribution to reverse degradation trends in a heavily grazed Succulent Karoo rangeland in South Africa. Over 3 years, the effects of the manure application were compared with areas planted with mature shrubs as a benchmark for a predisturbance vegetation structure and with four popular rehabilitation techniques: (1) livestock exclusion; (2) brushpacking (coverage of dead shrubs); (3) mineral fertilizing; and (4) microcatchment construction. Manure was, besides planting, the only treatment that resulted in a significant increase in drought‐resistant vegetation cover, but it compromised the dominance of native vegetation. In the manure plots, a pasture‐like vegetation of non‐native forage plants (which germinated mainly from seeds in the dung), developed (foremost Atriplex semibaccata) . Manure application counteracted erosion as effectively as the planted shrubs and brushpacks. Expected negative side effects such as a decrease in plant species richness or salinization of topsoil were not detected. We also checked the potential of topsoil salinization by the halophytic A. semibaccata and found it to be low. For sites where a decrease in grazing pressure is unrealistic under current land tenure, redistribution of manure should be further explored to mitigate acute symptoms of degradation. Copyright © 2013 John Wiley & Sons, Ltd.